Consequences of EU Politicisation for Voting in National Elections - Lobo, Marina Costa (2023)
In this Chapter, the conclusions of the research in the book as a whole are discussed. The book provides very strong multimethod evidence of the ability of voters to express their EU preferences when selecting national representatives at legislative elections, and how media and parliamentary parties condition it. Our double perspective on EU politicisation in the media and parliamentary debates lead to novel findings on the concept. In terms of salience and contestation, we found that the media and parliamentary debates follow different logics, with contestation being substantially higher in the media than in Parliaments. In terms of EU dimensions, we found that it is mostly policies being discussed in relation to the EU in both arenas. Yet, in this respect there are differences between countries: while Germany and Ireland discuss EU policies per se to a larger extent, in Southern Europe EU policies are discussed in relation to domestic issues. Looking at the consequences of politicisation, through experimental analysis, it is established that EU attitudes are a cause rather than a consequence of voting behaviour. Using observational data, we find that EU attitudes matter for both main mainstream and challenger parties, for parties which are Eurosceptic but also pro-EU parties, even if they do not replace the importance of the left-right dimension. Politicisation in both media and parliamentary debates are associated with the strength of EU issue voting. We conclude that the national channel of EU accountability, and namely the domestic institutions which contribute to it, need to be placed at the centre of the debate on how to hold the EU accountable.